Life Table Parameters and Digestive Enzyme Activity of Spodoptera littoralis (Boisd) (Lepidoptera: Noctuidae) on Selected Legume Cultivars - Seyed Ali Hemmati; Parviz Shishehbor; Lukasz L. Stelinski (Insects, 2022)
Spodoptera littoralis (Boisd) is a highly destructive pest that attacks a large number of economically important crops. We examined life table parameters as well as activity of major digestive enzymes of S. littoralis larvae in response to protein and starch contents across 11 legume cultivars to identify potential resistance traits. The results showed that S. littoralis reared on the common bean, Arabi, displayed the highest intrinsic rate of increase (r), while the lowest was recorded on the cowpea, Mashhad. Also, the highest net reproductive rate (R0) was obtained in those insects reared on the Arabi cultivar. Larvae displayed the highest and lowest proteolytic activities when fed on Mashhad and Arabi cultivars, respectively. The highest amylolytic activity was quantified in larvae that fed on the Arabi and 1057 cultivars, while the lowest occurred in larvae feeding on Yaghout and Mashhad cultivars. Developmental time of S. littoralis larvae was negatively correlated with protein content, while amylolytic activity was positively correlated with starch content of legumes. Our findings indicate that Arabi was a susceptible cultivar, while Mashhad exhibited tolerance traits against S. littoralis. These results should facilitate selection of legume cultivars for production or breeding efforts that involve S. littoralis management.